2022
DOI: 10.1038/s41598-022-19980-1
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of dry needling in patients with chronic low back pain: a prospective, randomized, single-blinded study

Abstract: Dry needling (DN) is a standard procedure for treating musculoskeletal disorders. However, there are no clear recommendations for using DN in low back pain (LBP). Therefore, this study aimed to assess the effectiveness of the novel DN program for reducing pain intensity and improving functional efficiency in patients with chronic LBP. A group of 40 patients with chronic LBP due to the L5-S1 discopathy were eligible and randomized into experimental (n = 20) and control (n = 20) groups. The DN program was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
(18 reference statements)
0
14
0
4
Order By: Relevance
“… 10 , 11 , 47 It is not uncommon to see investigations where needle retention time varies from less than 10 minutes, 48 to 20 minutes, 4 or even up to 60 minutes. 49 What's remarkable is that despite the variation, each of the above studies reported decreases in pain and disability after DN. While needle retention time is just a single component of the overall dosage parameters for EDN, being able to use the same amount of time across studies can help better inform clinicians and provide a basis for future studies.…”
Section: Discussionmentioning
confidence: 98%
“… 10 , 11 , 47 It is not uncommon to see investigations where needle retention time varies from less than 10 minutes, 48 to 20 minutes, 4 or even up to 60 minutes. 49 What's remarkable is that despite the variation, each of the above studies reported decreases in pain and disability after DN. While needle retention time is just a single component of the overall dosage parameters for EDN, being able to use the same amount of time across studies can help better inform clinicians and provide a basis for future studies.…”
Section: Discussionmentioning
confidence: 98%
“…The secondary outcomes will include: Total effective rate (as a dichotomous outcome): defined as the proportion of participants with a clinically relevant improvement according to a predefined change in validated depressive symptom and pain intensity rating scales at the end of the treatment period. Back pain-related function: measured as a continuous variable on any validated scale such as the Roland-Morris Disability Questionnaire (RMDQ), 32 Oswestry Disability Index (ODI), 33 Hanover Functional Ability Questionnaire (HFAQ), 34 or other rating scale with evidence of adequate validity and reliability at the end of the treatment period. Health-related Quality of Life (HRQoL): measured as a continuous variable on any validated HRQoL scale such as the Medical Outcomes Study 36/12-Item Short-Form Health Survey (SF-36/12), 35 , 36 Brief Form of the World Health Organization’s Quality of Life Questionnaire (WHOQOL-BREF), 37 Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q), 38 Nottingham Health Profile (NHP), 39 or other well-recognized HRQoL scales with evidence of adequate validity and reliability at the end of the treatment period.…”
Section: Methodsmentioning
confidence: 99%
“…2. Back pain-related function: measured as a continuous variable on any validated scale such as the Roland-Morris Disability Questionnaire (RMDQ), 32 Oswestry Disability Index (ODI), 33 Hanover Functional Ability Questionnaire (HFAQ), 34 or other rating scale with evidence of adequate validity and reliability at the end of the treatment period. 3.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…So far, many studies have investigated different treatment approaches for non-specific chronic low back pain 10 13 . Although there are many contradictions, such as the degree of effectiveness and their possible side effects, regarding the selection of the most favorable treatment approach, there is an agreement that such advices as bed rest, which were previously recommended for acute back pain, are not very effective for this type of back pain 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many contradictions, such as the degree of effectiveness and their possible side effects, regarding the selection of the most favorable treatment approach, there is an agreement that such advices as bed rest, which were previously recommended for acute back pain, are not very effective for this type of back pain 10 , 11 . Based on the research findings, various treatment approaches have been used to treat back pain, including drug therapy 12 , dry needling 13 , 14 , kinesiotaping 15 , 16 , laser therapy 17 , 18 , massage, hydrotherapy 19 , 20 , ultrasound 21 , 22 , and finally surgery 23 25 . Based on these studies [], it has been determined that each of these treatment methods can have immediate or delayed effects on the recovery of people with low back pain.…”
Section: Introductionmentioning
confidence: 99%